Mass spectrometry-based analyses showing the effects of secretor and blood group status on salivary N-glycosylation. Issue 1 (December 2015) - Albertolle, Matthew; Hassis, Maria; Ng, Connie; Cuison, Severino; Williams, Katherine; Prakobphol, Akraporn; Dykstra, Andrew; Hall, Steven; Niles, Richard; Ewa Witkowska, H.; Fisher, Susan
Abstract Background The carbohydrate portions of salivary glycoproteins play important roles, including mediating bacterial and leukocyte adhesion. Salivary glycosylation is complex. Many of its glycoproteins present ABO and Lewis blood group determinants. An individual's genetic complement and secretor status govern the expression of blood group antigens. We queried the extent to which salivary glycosylation varies according to blood group and secretor status. First, we screened submandibular/sublingual and parotid salivas collected as ductal secretions for reactivity with a panel of 16 lectins. We selected three lectins that reacted with the largest number of glycoproteins and one that recognized uncommon lactosamine-containing structures. Ductal salivas representing a secretor with complex blood group expression and a nonsecretor with a simple pattern were separated by SDS-PAGE. Gel slices were trypsin digested and the glycopeptides were individually separated on each of the four lectins. The bound fractions were de-N -glycosylated. LC–MS/MS identified the original glycosylation sites, the peptide sequences, and the parent proteins. Results The results revealed novel salivaryN -glycosites and glycoproteins not previously reported. As compared to the secretor, nonsecretor saliva had higher levels ofN -glycosylation albeit with simpler structures. Conclusions Together, the results suggested a molecular basis for inter-individual variations in salivary protein glycosylation with functional implications for oral health.